On-chip enzymatic microbiofuel cell-powered integrated circuits. Issue 10 (26th April 2017) - Mark, Andrew G.; Suraniti, Emmanuel; Roche, Jérôme; Richter, Harald; Kuhn, Alexander; Mano, Nicolas; Fischer, Peer
Abstract : A CMOS based digital circuit that is powered by an integrated on-chip enzymatic microbiofuelcell. Abstract : A variety of diagnostic and therapeutic medical technologies rely on long term implantation of an electronic device to monitor or regulate a patient's condition. One proposed approach to powering these devices is to use a biofuel cell to convert the chemical energy from blood nutrients into electrical current to supply the electronics. We present here an enzymatic microbiofuel cell whose electrodes are directly integrated into a digital electronic circuit. Glucose oxidizing and oxygen reducing enzymes are immobilized on microelectrodes of an application specific integrated circuit (ASIC) using redox hydrogels to produce an enzymatic biofuel cell, capable of harvesting electrical power from just a single droplet of 5 mM glucose solution. Optimisation of the fuel cell voltage and power to match the requirements of the electronics allow self-powered operation of the on-board digital circuitry. This study represents a step towards implantable self-powered electronic devices that gather their energy from physiological fluids.